2012
DOI: 10.1155/2012/954343
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of a Chronically Recurring Case of Cervical Mucocele in a German Shepherd Dog

Abstract: A-six-year old male German shepherd dog with swelling and enlargement of the intermandibular and cervical region with a duration of nearly one year was referred to the small animal veterinary hospital, Islamic Azad University of Tabriz. Based on the history, clinical findings, and laboratory investigations, the animal was diagnosed as having cervical mucocele with the involvement of the left sublingual and mandibular salivary glands. Surgical treatment consisting of the excision of the involved gland/duct comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The treatment of this disease is based on surgical extraction (1,8,11,12). Drainage is not sufficient to treat sialocele (1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of this disease is based on surgical extraction (1,8,11,12). Drainage is not sufficient to treat sialocele (1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…2,3,7 The rate of sialocele development may be further attenuated by absorption of extravasated saliva by surrounding tissues. 12 Where residual salivary tissue remains, development of a defect at a location independent of the initial rupture site could also be possible because sialography has previously demonstrated multiple defects within the same salivary chain. 1 A limitation of our study was the use of ultrasonography rather than CT in many of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…
sis. [7][8][9][10][11][12] Sublingual and mandibular sialoceles typically present as a nonpainful fluctuant mass in the intermandibular, cranioventral cervical, sublingual, or pharyngeal region. 8,13,14 While many are clinically inconsequential, dysphagia, ptyalism, snoring, coughing, stridor, inspiratory dyspnea, or cyanosis may occur in animals with pharyngeal or sublingual swelling sufficient to cause pharyngeal obstruction.
…”
mentioning
confidence: 99%
“…In this study, presence of no significant pathological abnormalities, histopathologically, pointed out the possibility of physical trauma as an etiological factor for the development of sialocele. Earlier studies reported mild atrophy and hemorrhage of glandular tissue on histology in dogs with salivary mucocele (Kazemi et al 2012;Shivaraju et al 2018).…”
Section: Mandibular and Sublingual Sialoadenectomy To Treat Cervical mentioning
confidence: 93%